The biomechanical overload of the upper limb: a neglected occupational hazard in animal facility operators. Issue 3 (4th March 2017) - Occhionero, Vincenzo; Ghersi, Rinaldo; Prandini, Lucio; Korpinen, Leena; Gobba, Fabriziomaria
Abstract: Data on biomechanical overload of the upper limb in animal facility operators are currently scanty. We decided to study this risk in a university animal facility. Eleven different tasks performed by operators were identified. For each of them, the biomechanical overload of the upper limb was evaluated by applying 4 different methods frequently used, hypothesising a task duration of 4 and 8 h. Then two 'typical' real working days of the examined facility were reconstructed, and the risk for operators was calculated using the OCRA Index, Checklist and Mini-Checklist. Considering the specific tasks, the results show some difference among methods, but the overall results show an acceptable/slight risk of biomechanical overload of the upper limb in animal facility operators during typical working days. Practitioner Summary: Upper limb biomechanical overload (UL-BO) is a neglected risk in animal facilities. In a university facility, 11 different tasks were identified, and 2 typical working days were analysed. Even if some task at increased risk may exist,  during typical working days,  the overall results show that the risk of UL-BO in operators can be considered usually acceptable or, at worst, slight.